A study on the effects of promotion towards job satisfaction within public organization: a case study at Kastam Diraja Ayer Keroh, Malacca / Nurhanani Kamaludin - Kamaludin, Nurhanani (Faculty of Administrative Science and Policy Studies, 2004)
This research is about the effects of promotion towards job satisfaction. The objective of this research is to know whether the effects of the promotion have association with job satisfaction. Promotion is the way to recruit the employees internally or in the other words, it is internal recruitment, which recruit individual from within the organization to fulfill vacancies. Job satisfaction is a collection of the employees feeling about their jobs. The researcher has chosen KASTAM Di Raja, Ayer Keroh, Malacca to done this research. The respondents are choosing randomly. The findings of the data have been analyzed through SPSS. The associations have been shown in the frequency, cross tabulation and descriptive statistics. The finding shows that only conflict and promotional policy have association with job satisfaction in the KASTAM Di Raja, Ayer Keroh, Malacca organization. The recommendations have been given which is how the organization can do to ensure that the promotion can be practices successfully.